Knowledge creation in community development institutional change in Southeast Asia and Japan - Nishihara, Ayano Hirose; Matsunaga, Masaei; Nonaka, Ikujirō; Yokomichi, Kiyotaka (Palgrave Macmillan, 2018)
"This book explores how public organizations and not-for-profit organizations (NPO) can be more collaborative, innovative and effective in solving social issues in both developing and developed countries. "Social innovation," led by social entrepreneurs and/or social enterprises, emerged in the late 1990s, and spread in 2000s. As the West faced management failures, demand increased for corporations to take on more social responsibility. Based on intensive research on social innovation processes at the municipal and the community level in Indonesia, Philippines, Thailand, Vietnam, and Japan, the book analyses the factors that affected the most effective and efficient social innovations. "-- Provided by publisher.